Urgensi Mata Kuliah Pengembangan dan Praktik Pembelajaran PPKn pada Calon Guru Sekolah Dasar - Retnasari, Lisa; Suyitno, Suyitno; Arif, Dikdik Baehaqi; Suroto, Suroto (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
Civic Education is a compulsory subject that must be taken by students from elementary school to college to create a smart and good generation. However, it is often underestimated due to the paradigm of a boring subject. As prospective elementary school educators, students certainly need to equip themselves to create professional competence, namely mastery of teaching material comprehensively and broadly. This is done through the P3PPKn elementary school course in semester IV. The purpose of this study was to determine and analyze the understanding of the basic concepts of elementary school Civics for prospective educators through the P3PPKn SD course. The research method used is descriptive qualitative. The research subjects were PGSD FKIP UAD fourth-semester students by random sampling. Data collection techniques were observation, interviews with questionnaires, and documentation. Data analysis techniques using data triangulation. The results of the research are that PGSD FKIP UAD students have a good level of understanding of the basic concepts of elementary school Civics. This is indicated by the number of respondents agreeing with the importance of prospective educators understanding the concept material of Civics comprehensively. To avoid misconceptions in the delivery of material. Given the new paradigm, namely to form civic intelligence, civic responsibility, and civic participation. In addition, the basic concepts of Civics material based on the findings are Pancasila, Unity in Diversity, UUD NRI 1945 and NKRI which must be the main knowledge of prospective elementary school educators. Prospective educators through P3PPKn courses not only learn about the concept of material but how to teach it through the learning design that has been prepared. Therefore, the quality of P3PPKn courses is important to improve in preparing professional educators by the challenges of the times.